“There's a Kind of Comfort in Identifying, But Visibility is a Double‐Edged Sword”: Framing LGBTQIA+ Finding Aid Work within Queer Theory - Wagner, Travis; Allgood, Evan (Proceedings of the Association for Information Science and Technology, 2025)
ABSTRACT Making visible LGBTQIA+ materials within cultural heritage institutions requires understanding the potentially positive and negative consequences of queer visibility. Deploying findings from interviews with 29 archivists, this paper explores how practitioners responsible for creating and managing finding aids for LGBTQIA+ archives navigate their work. This paper reveals how participants navigated clear understandings of the historical and theoretical implications rooted in naming queer identities within archival records. This paper places these configurations of archival description and queer visibility in conversation with both the reparative and anti‐social lenses of queer theory. The first posits that expanding queerness in finding aids ensures a more queer‐inclusive future, while the latter contends that inconsistencies between social support of queer individuals and the policies enacting such support remain too vast to ensure safety. The paper concludes with theoretical and praxis‐based implications for this work in an era of automation and governmental backlash.